The Evolutionary Conserved γ-Core Motif Influences the Anti-Candida Activity of the Penicillium chrysogenum Antifungal Protein PAF - Sonderegger, Christoph; Váradi, Györgyi; Galgóczy, László; Kocsubé, Sándor; Posch, Wilfried; Borics, Attila; Dubrac, Sandrine; Tóth, Gábor K.; Wilflingseder, Doris; Marx, Florentine (Frontiers in Microbiology, 2018)
Small, cysteine-rich and cationic antimicrobial proteins (AMPs) from filamentous ascomycetes represent ideal bio-molecules for the development of next generation antifungal therapeutics. They are promising candidates to counteract resistance development and may complement or even replace current small molecule-based antibiotics in the future. In this study, we show that a 14 amino acid (aa) long peptide (Pγ) spanning the highly conserved γ-core motif of the Penicillium chrysogenum antifungal protein PAF has antifungal activity against the opportunistic human pathogenic yeast Candida albicans. By substituting specific aa we elevated the positive net charge and the hydrophilicity of Pγ and created the peptide variants Pγvar and Pγopt with ten-fold higher antifungal activity than Pγ. Similarly, the antifungal efficacy of the PAF protein could be significantly improved by exchanging the respective aa in the γ-core of the protein by creating the protein variants PAFγvar and PAFγopt. The designed peptides and proteins were investigated in detail for their physicochemical features and mode of action, and were tested for cytotoxicity on mammalian cells. This study proves for the first time the important role of the γ-core motif in the biological function of an AMP from ascomycetes. Furthermore, we provide a detailed phylogenetic analysis that proves the presence and conservation of the γ-core motif in all AMP classes from Eurotiomycetes. We emphasize the potential of this common protein motif for the design of short antifungal peptides and as a protein motif in which targeted aa substitutions enhance antimicrobial activity.